The Dynamic association of Energy, Environmental Management Accounting and Green Intellectual Capital with Corporate Environmental Performance and Competitive - Sidik, Morni Hayati Jaafar; Yadiati, Winwin; Lee, Hoyoung; Khalid, Nadeem (International Journal of Energy Economics and Policy, 2019)
The current study aims to investigate the impact of energy efficiency, green intellectual capital and environmental management accounting system on environmental performance and competitive advance in Indonesia manufacturing industry. In doing so, we utilized the sophisticated methodology of PLS-SEM to identify the potential association among the variables of interest. Even after the growing consciousness for environmental management, there exist some companies that consider the acceptance of environmental trend as an obstacle to their growth and performance. The results confirm that all selected variables have a positive and significant impact on environmental performance and competitive advantage in the manufacturing industry in Indonesia. Moreover, the outcomes of the PLS-SEM confirm that environmental performance and competitive advantage have positively and expressively impacted by green intellectual, energy efficiency and environmental accounting system. In general, the results of partial least square confirm that the three factors, i.e., green intellectual capital, energy efficiency, and environmental accounting management system are the positive and significant contributor to enhance the environmental performance and competitive advantage of the firm in Indonesia manufacturing industry. Keywords: Energy efficiency, green intellectual capital, environmental performance, competitive advantage, Indonesia. JEL Classifications: Q55, Q50, O34 DOI: https://doi.org/10.32479/ijeep.8283